Keberlanjutan Kawasan Hutan Dengan Tujuan Khusus (KHDTK) Kepau Jaya di Desa Kepau Jaya Kecamatan Siak Hulu Kabupaten Kampar - Tasman Adi; Ridwan Manda Putra; Defri Yoza (Pelantar Press, 2025)
This study aims to evaluate the sustainability level of management of the Kepau Jaya Special Purpose Forest Area (KHDTK) in Kampar Regency, Riau Province, based on four main dimensions: ecological, economic, socio-cultural, and legal and institutional. The analytical method used was Multidimensional Scaling (MDS) with the Rap-SPFA tool, which was modified to assess multidimensional sustainability status. The analysis was conducted by measuring the sustainability index of each dimension using a scale of 0-100. The results showed that the overall level of sustainability was in the less sustainable category with an index of 49.56. The ecological, economic, and legal and institutional dimensions are the main focus in management, while the socio-cultural dimension is in the moderately sustainable category with an index of 68.03. The proposed sustainable management strategies include ecosystem-based zoning, utilization of non-timber forest products (NTFPs), increased community involvement, and institutional strengthening through inter-stakeholder synergies. Improving infrastructure, NTFP-based economic development, and community education are prioritized in an effort to support more effective management. The implementation of this strategy is expected to improve the sustainability of Kepau Jaya KHDTK management while improving the welfare of the surrounding community